Information Sources in Patents. - Adams, Stephen (Guides to Information Sources., 2011)
Since the publication of the 2nd edition additional countries especially in Asia have become more prominent in industry. This completely revised edition takes account of the changing information scene e.g. in new chapters like BRIC nations (Brazil, Russia, India, and China), Asia and regional patent systems or Sources for legal status searching. This is an essential reference tool for academic librarians and information specialists as well as anyone needing to know where and how patent information can be found.